Analisis Nilai Tambah dan Kelayakan Finansial pada Usaha Produksi Extract Powder Kunyit - Ariesta Putra, Pande Ketut Raka; Mulyani, Sri; Sedana Yoga, I Wayan Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
Turmeric extract powder was processed product of turmeric which were produced in powder form. This study aimed to determine the value added obtained in the process of producing extract powder, knowing the financial feasibility obtained from the productin process of turmeric into extract powder products. The financial feasibility study uses the calculation of profit and loss analysis, Net Present Value, Internal Rate of Return, Net B / C Ratio, Payback Period, and Break Event Point and Hayami method to determine the added value.. The business of extract powder was feasible to obtain, and the Net Present Value was Rp. 290.897.909. The Internal Rate of Return of 13% showed that the rate of return was greater the specified Bank interest rate. Payback Period for 1 year 2 months and B/C Ratio of 1,68. The value added of extract powder obtained a value of Rp. 20.000 per kg, the income value added ratio was 57,14%. The sensitivity analysis scenario showed that both an increased in operational costs of 3%-6% and income decreased by 3%-6% resulting in positive NVP. Therefore, the turmeric extract powder business was feasible. Keywords : Turmeric, extract powder, value added analysis, and financial feasibility